A Field Study of Arab Data Journalism Practices in the Digital Era. (7th February 2021) - Fahmy, Nagwa; Attia, Maha Abdul majeed
ABSTRACT: This research paper presents an analysis of the state of data journalism practice in the Arab world through the use of the field theory approach. It is based on the analyzed results from a survey of Arab journalists conducted by the Arab Data Journalists Network (ADJN) in 2017. This paper discusses the factors affecting the practice and development of Arab data journalism. It sheds light on the potentials and challenges of practicing data journalism in the Arab world, especially in terms of required resources as well as the cultural, socioeconomic, and institutional context in the Arab journalism ecosystem. As an indication of a clear interest in this field, a significant amount of Arab journalists are interested in applying for data journalism training and fellowships. However, the business model of most Arab media organizations, which struggle from certain financial or political agendas, makes these organizations less interested in upgrading the quality of their content provided to their audience. Accordingly, they do not care about adopting new methods in presenting in-depth and data-driven content. This study concludes with a theoretical model regarding the state of data journalism in Arab countries and suggests several applicable ways to develop data journalism practices and education.